Successful surgical treatment for a thrombus straddling a patent foramen ovale: a case report - Nemoto, Atsushi (BioMed Central, 2013)
Paradoxical embolism (PDE) occurs after embolic material passes from the venous to the arterial circulation through a right-to-left shunt, which is frequently a patent foramen ovale (PFO). We describe the case of a patient with deep venous thrombosis and an intracardiac thrombus straddling a PFO and who was successfully treated with an emergency surgery.